Cataract Surgery in Vogt — Koyanagi — Harada Syndrome (Clinical Case) - I. Yu. Razumova; A. S. Stoyukhina; L. Alharki; E. N. Korobov; E. D. Khachaturova (Oftalʹmologiâ, 2024)
The article describes a clinical case of the Vogt — Koyanagi — Harada syndrome with an ophthalmic manifestations: bilateral granulomatous panuveitis with funnel-shaped serous retinal detachment complicated by cataracts, clinical manifestations in the form of alopecia and poliosis, as well as the results of phacoemulsification with IOL implantation.